Electronic health records in nursing from 2000 to 2020: A bibliometric analysis - Luan, Ze; Zhang, Zhiru; Gao, Yanan; Du, Shiyuan; Wu, Nan; Chen, Yulu; Peng, Xin (Frontiers in Public Health, 2023)
Background: Electronic health records (EHR) is the longitudinal data generated by patients in medical institutions and recorded by electronic medical information systems in the form of digital, which is also the most widespread application of big data in medicine. The purpose of this study was to explore the application of electronic health records in the field of nursing, and determine the current research status and hotspots. Methods: A bibliometric analysis of electronic health records in nursing was undertaken from 2000 to 2020. The literature comes from the Web of Science (WOS) core database. We used CiteSpace (version 5.7 R5; Drexel University), which is a Java-based software that especially visualized collaborative networks and research topics. A total of 2619 records were included in the study Results: We found that academic activities increased significantly. The Journal of American Medical Informatics Association is the most cited journal. The relevant literature also focuses on the fields of health care science and services, medical informatics. The use of electronic health records for long-term care, mobile application, inpatient falls, and advance care planning has been researching hotspots in recent years. Conclusion: This article provides a comprehensive knowledge structure and development history of electronic health records, helps us understand its application in the field of nursing, and provides ideas for its development and widespread use.